Uma luta de gigantes? Judiciário e legislativo no tratamento institucional da união homoafetiva - Amorim, Germanna Gabriella (Universidade Federal Rural do Semi-Árido, 2021)
The phenomenon of judicial activism is based on the fact that the Judiciary must guarantee the realization of fundamental rights, however, it permeates the problem that considers the exceeding of the limits of action of the Powers, as established by the legal system. The discussion revolves around the appropriate locus to discern the matter, having on the one hand the Legislative Power, a legitimate democratic space to discuss and create law, and on the other, the Judiciary Power, charged with the mission of guaranteeing fundamental rights. In this sense, this research aims to verify the existence of interinstitutional tension between the Powers, taking as its object of analysis the case of same-sex union recognized by the Supreme Court, and the institutional responses articulated in the National Congress. In this aspect, qualitative, quantitative and descriptive research is developed, adopting the deductive methodology, through bibliographic and documental analysis, through jurisprudence, legislation and law proposals that were presented in the National Congress. The theme is developed in two parts. The first is intended for the theoretical study of judicial activism, which also addresses the legal protection of the stable union, having as its culmination the decision of ADI 4.277 and ADPF 132. In the second part, the data collected are presented and analyzed quantitatively and qualitatively. through the research, to then present the systematization and analysis of the proposals. In the end, it was concluded that it cannot be said that there is significant tension between the Powers, leaving it clear that the theme of homo-affective union is marked by ideological, cultural and religious expression, as well as by clear party-political positions on the part of representatives of the people in the National Congress. This scenario certainly results in a polarization of positions that does not converge to a final outcome, the STF's word prevailing for the time being
Keywords: Ativismo Judicial; Poder Judiciário; Poder Legislativo; Tensão Interinstitucional; União Homoafetiva; Judicial activism; Judicial Power; Legislative Power; Interinstitutional tension; Homoaffective union; CIENCIAS SOCIAIS APLICADAS::DIREITO